Pengaruh Variasi Menu, Store Atmosphere dan Harga Terhadap Keputusan Pembelian pada Burjo Polopes Sragen - Anisa Dini Ekawati; Sumaryanto (Teewan Journal Solutions, 2025)
Burjo Polopes is one of the restaurants that is currently popular with the public in the city of Sragen. Burjo here is different from other burjos because it has a comfortable atmosphere for gathering with friends or family. The problem in this study is whether there is an influence of menu variation, store atmosphere, and price on purchasing decisions. The purpose of this study is to determine the significance of the influence of menu variation, store atmosphere, and price on purchasing decisions. The use of this study as a consideration for consumers to decide to purchase at Burjo Polopes Sragen. The hypothesis in this assessment is suspected that there is a significant influence between menu variation, store atmosphere, and price on purchasing decisions. This study uses a survey method conducted on consumers of Burjo Polopes Sragen. The data required is a general description of Burjo Polopes Sragen, respondents' responses to menu variation, store atmosphere, price, and purchasing decisions. Data sources are primary and secondary data. Data collection technique by distributing questionnaires. The sampling technique uses the accidental sampling method with 100 respondents. The results of the t-test show that menu variations have a significant effect on purchasing decisions, store atmosphere has a significant effect on purchasing decisions, and prices have a significant effect on purchasing decisions. The results of the F test show that there is a significant effect of menu variations, store atmosphere, and prices on purchasing decisions. The results of the determination coefficient calculation obtained a value of (R2) = 0.591, meaning that 59.1 percent of purchasing decisions are influenced by menu variations, store atmosphere, and prices.